AN OUTBREAK OF SCRUB TYPHUS IN A REMOTE VILLAGE-AN OVERVIEW - BHARATHI, M.; KALYANI, C. SIVA; SIRISHA, T. (International Journal of Current Pharmaceutical Research, 2023)
Objective: An outbreak of scrub typhus was declared by Public Health authorities in our district in October, 2022. To investigate this a team of experts from Microbiology, SPM, Medicine and Pediatric Medicine was sent to the place of outbreak and they observed that there was heavy vegetation, stagnant water, dwellings heavily infested with rodent population. There was heavy rain in the past two weeks in the district. To investigate the cause of sudden upsurge of febrile illness cases. Methods: Blood samples were collected from 28 persons who were symptomatic with fever/headache/diarrhea/rash and myalgia to do tests for Scrub typhus, Typhoid fever, Malaria, Dengue, Complete blood count, CRP, LFT and KFT. The samples which were positive for Scrub typhus in rapid test kits were subjected for IgM ELISA to confirm scrub typhus. Results: Seven of twenty-eight patients tested positive for scrub typhus by rapid test (25%), and four of them were positive by IgM ELISA (14.28%). Three patients were Widal-positive (10.7%). More than half samples showed increased CRP levels (53.57%). Thrombocytopenia and mild leucocytosis was observed in scrub typhus cases (42.85%) as well as in typhoid cases. Conclusion: Any outbreak during monsoon should be investigated thoroughly not only for the specified disease but also for all infectious diseases that are prevalent in that area.